Do intellectual capital and financing matter for the profitability of the Islamic banking industry in Indonesia?. (10th November 2022) - Fitri, Fauziah Aida; Syukur, Muhammad; Majid, M. Shabri Abd.; Farhana, Intan; Hatta, Fakhri
In Indonesia, the Islamic banking industry has been experiencing growth since its establishment in 1992. Although its profitability has declined slightly due to Covid-19, Islamic banks have recorded higher profitability than the average banking industry nationwide. Motivated to identify the factors that determine the banking profitability, this research empirically tests the contribution of intellectual capital (measured by VAIC TM ), banks' liquidity (financing-to-deposit ratio), and financing ineffectiveness (non-performing financing or NPF) to the profitability (return on assets or ROA) of Islamic banks in Indonesia. We gathered data from the published financial information comprising a total of 130 observation years. The result shows that intellectual capital, banks' liquidity, and financing ineffectiveness impacted the profitability of Islamic banks in Indonesia. The findings of this study provide policy implications for Indonesia's Islamic banks to apply prudential banking principles in their financing activities.